2021
DOI: 10.3389/fcell.2021.698047
|View full text |Cite
|
Sign up to set email alerts
|

CAM-DR: Mechanisms, Roles and Clinical Application in Tumors

Abstract: Despite the continuous improvement of various therapeutic techniques, the overall prognosis of tumors has been significantly improved, but malignant tumors in the middle and advanced stages still cannot be completely cured. It is now evident that cell adhesion-mediated resistance (CAM-DR) limits the success of cancer therapies and is a great obstacle to overcome in the clinic. The interactions between tumor cells and extracellular matrix (ECM) molecules or adjacent cells may play a significant role in initiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 167 publications
(162 reference statements)
0
12
0
Order By: Relevance
“…The strong binding of the ECM proteins to cancer cells allows cancer cells to escape cytotoxic drugs through a process known as cell-adhesion-mediated drug resistance (CAM-DR) [ 79 ]. This CAM-DR is mediated by various adhesion molecules, such as integrins [ 157 ], C-X-C motif chemokine receptors (CXCR) [ 158 ], and β-catenin [ 159 ]. Waldschmidt et al observed increased cytotoxicity when co-culturing stromal cells and multiple myeloma cells with bortezomib and the CXCR4 inhibitor plerixafor [ 160 ].…”
Section: Mechanisms Of Stroma-mediated Therapy Resistancementioning
confidence: 99%
“…The strong binding of the ECM proteins to cancer cells allows cancer cells to escape cytotoxic drugs through a process known as cell-adhesion-mediated drug resistance (CAM-DR) [ 79 ]. This CAM-DR is mediated by various adhesion molecules, such as integrins [ 157 ], C-X-C motif chemokine receptors (CXCR) [ 158 ], and β-catenin [ 159 ]. Waldschmidt et al observed increased cytotoxicity when co-culturing stromal cells and multiple myeloma cells with bortezomib and the CXCR4 inhibitor plerixafor [ 160 ].…”
Section: Mechanisms Of Stroma-mediated Therapy Resistancementioning
confidence: 99%
“…Collectively, these results suggest that the bisected N-glycans on β4 integrin negatively regulate α6β4 integrin-mediated resistance to DOX and provide further evidence that N-glycans on β4 integrin play a pivotal role in the DOX resistance. The prevention of apoptosis often confers drug resistance [8,29]. Therefore, we hypothesized that β4 integrin-mediated DOX resistance might occur through the prevention of apoptosis and then examined the cleavage of caspase-3, a marker of cells undergoing apoptosis (Figure 1).…”
Section: α6β4 Integrin-mediated Dox Resistance Is Abolished By the Ad...mentioning
confidence: 99%
“…Importantly, the adhesion of MM cells to BMSCs and/or the extracellular matrix triggers the NF-κB-dependent transcription and secretion of cytokines such as IL-6, tumor necrosis factor-α, and osteopontin in BMSCs, which further stimulates development of drug resistance or so-called cell adhesion-mediated drug resistance (CAM-DR) [ 24 , 25 , 26 ]. Notably, CAM-DR plays a significant role in the development of drug resistance in MM [ 7 , 26 , 27 ]. Therefore, targeting CAM-DR is now thought to be a promising option to improve the prognosis of MM patients.…”
Section: Hematopoietic Stem Cell (Hsc) Niche and MM Nichementioning
confidence: 99%
“…Research also indicates that the BMM plays an important role in the drug resistance mechanism of MM. In particular, adhesion between MM cells and BM stromal cells mediated by adhesion molecules induces cell adhesion-mediated drug resistance (CAM-DR) [ 7 ]. Analyses of the role of mitochondria in cancer cells, including MM cells, has revealed that the mechanism leading to drug resistance involves the exchange of mitochondria between cells (mitochondrial transfer) via tunneling nanotubes (TNTs) within the MM niche [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%